Signature feedback practices in the creative arts: integrating feedback within the curriculum. Issue 6 (18th August 2022) - Pitt, Edd; Carless, David
Abstract: Without teacher and student feedback literacy, it is difficult for feedback processes to fulfil their potential. Feedback literacy development within the arts or humanities is, however, under-researched. The current study fills this gap by illustrating how educators in the performative creative arts designed signature feedback practices to facilitate the development of student feedback literacy. Opportunities for feedback literacy development were created via learning cultures that embedded emotional and relational support, discussed work-in-progress, and promoted peer feedback. Focus groups with educators highlighted how integrated assessment design and signature feedback practices provided opportunities for collaborative, critical and open learning environments conducive to the development of student feedback literacy. Students were afforded ongoing opportunities to perform their work-in-progress and see first-hand the work of peers, facilitating space in the curriculum for meaningful dialogue surrounding the enactment of feedback. Questionnaire data indicated that students understood the role of feedback in their learning but sometimes struggled to generate feedback for their peers and apply it to their own work. The main significance of the research lies in showing how signature feedback practices enable the integration of curriculum and assessment and carry potential to support the development of teacher and student feedback literacy.